The Influence of Value theory in Orthodox and Heterodox Economic Journals (Papeles, 2019)
The theory of value is an economic subject that has been investigated by the greatest economic thinkers throughout history, both orthodox and heterodox. Descriptive research is carried out based on journals specialized in economic matters of the already mentioned mainstreams about the study and the emphasis they have on the subject of value theory through its different volumes. Different papers were chosen. This research seeks to know the frequency with which the theory of value is addressed in its various articles and thus verify the importance and use of the theory of value in the journals nowadays.
Keywords: theory of value; orthodox; heterodox; economic theory